Patient-generated Digital Images after Pediatric Ambulatory Surgery - Miller, Matthew W.; Ross, Rachael K.; Voight, Christina; Brouwer, Heather; Karavite, Dean J.; Gerber, Jeffrey S.; Grundmeier, Robert W.; Coffin, Susan E. (Applied Clinical Informatics, 2016)
To describe the use of digital images captured by parents or guardians and sent to clinicians for assessment of wounds after pediatric ambulatory surgery.Subjects with digital images of post-operative wounds were identified as part of an ongoing cohort study of infections after ambulatory surgery within a large pediatric healthcare system. We performed a structured review of the electronic health record (EHR) to determine how digital images were documented in the EHR and used in clinical care.We identified 166 patients whose parent or guardian reported sending a digital image of the wound to the clinician after surgery. A corresponding digital image was located in the EHR in only 121 of these encounters. A change in clinical management was documented in 20% of these encounters, including referral for in-person evaluation of the wound and antibiotic prescription.Clinical teams have developed ad hoc workflows to use digital images to evaluate post-operative pediatric surgical patients. Because the use of digital images to support follow-up care after ambulatory surgery is likely to increase, it is important that high-quality images are captured and documented appropriately in the EHR to ensure privacy, security, and a high-level of care.Citation: Miller MW; Ross RK; Voight C; Brouwer H; Karavite DJ; Gerber JS; Grundmeier RW; Coffin SE. Patient-generated Digital Images after Pediatric Ambulatory Surgery
Keywords: Ambulatory care information systems; patient records; surgery; workflow; clinical images